The Effectiveness of Hawthorn (Ws-1442 Standardized Crataegus oxycantha Extract) Against Alcohol-Induced Brain Injury In Rat; Its Underlying Potential Mechanisms - Deniz, Gulsah Yildiz; Geyikoglu, Fatime; Erol, Hüseyin Serkan; Aslan, Merve (Research Square Platform LLC, 2024)
Abstract The herbal supplements can attenuate alcohol-related traumatic organ damages. In this study, we aimed to investigate the therapeutic role of hawthorn (SCE) against alcohol-induced neurotoxicity. Sprague Dawley rats received a single dose of ethanol (4.5 g/kg, intragastric) and were then administered orally standardized SCE for 20 days. At the end of experiment, brain samples were removed for biochemical, histological, immunofluorescence, histochemical and immunuhistochemical analyzes in rats. SCE significantly reduced the levels of 6-keto prostaglandin F1 alpha (6K-PGF1) and thromboxane B2 (TXB2), which were increased in brain by ethanol exposure. SCE administration ameliorated neuroinflammation and provided significant decreases the raised levels of Tumor necrosis factor-alpha (TNF-α) and Interleukin 1 beta (IL-1 β). Superoxide dismutase (SOD) and glutathione (GSH) contents were negatively correlated with the MDA concentration after oral adminstration of plant extract. Myelin damage and severe pathological findings following alcohol intoxication weren’t observed. Our study provide, the first evidence of effectiveness SCE in rat brain against alcohol injury. Its mechanisms may be related to improvement of vascular function, reduction in inflammatory reaction, antioxidative activity, anti-genotoxicity, myelin regeneration and also anti-apoptotic effects. In conclusion, SCE is a targeted and promising drug to treat brain necrosis due to alcohol usage. SCE seems to counteract the deleterious effects of ethanol on brain tissue through different cellullar and signaling mechanisms and thus can be used as a thearupatic practice against alcohol toxicity.
Keywords: 3. Good health